LICENSING AND LEGALIZATION OF TRADITIONAL MEDICINE TO ENSURE PUBLIC HEALTHH QUALITY - Lilik Pudjiastuti (Jurnal Dinamika Hukum, 2015)
Traditional medicine is a form of pharmaceutical ingredient which uses as medicine by the people. In public paradigm, traditional medicines is considering more secure and cheaper compare with patent medicine. The reason of such condition due to traditional medicines are made from materials of plants, animals, mineral galenic ingredients or mix of all those ingredients hereditary. In Indonesia the instrument control of traditional medicine conducted by regulation, license, supervision and legal enforcement. In practical, based on the surveillance result which conducted by BPOM found from 7.605 sample of traditional medicine, 1.867 (24.55%) of those are not fulfilled the standard because several reasons contain chemical ingredients, does not have distribution license, has long wrecked time and has unsuitable water content. This condition resulted due to the lack of ability of traditional medicine business to fulfill the requirement and obligation of license owner to conduct the medicine manufacture base on CPOTB.  Keywords: traditional medicine, license, legal enforcement.